REVIEW OF PURCHASING AND SELLING NFTS IN ISTIHSAN - Mohammad Farid Fad (UIN Walisongo Semarang, 2023)
AbstractSo far, NFTs have been defined as digital tokens that are shaped like ownership certificates for virtual and physical assets. These NFTs are usually traded online and are often paid for using cryptocurrencies, especially Ethereum. However, the problem is that in 2021 the MUI issued a fatwa that cryptocurrency is illegal. This is because it there are elements of qimar, dharar, and gharar. For this reason, it is necessary to study the methodology of Islamic law regarding Non-Fungible Tokens (NFT) through istihsan (juristic preference). This study uses a qualitative approach. The data were collected from library study, documentation and observation. In analyzing the data used descriptive-analytic analysis with the approach used is ushuliyah. This study revealed that from istihsan point of view, transactions using Non-Fungible Tokens are permitted. This is because, from Qiyas Khafi perspective, NFT is known as the underlying assets of the transaction. Up to the operational level, if qiyas khafi is of greater benefit, then qiyas jali may be abandoned. What is used is qiyas khafi to maintain the principles of maqasid shari'a. Therefore, within the istihsan framework, Non-Fungible Token transactions are allowed through qiyas khafi due to an element of greater benefit.Keywords: Non-Fungible Token Transaction; Istihsan; Maqasid Shari’a, AbstrakSelama ini NFT didefinisikan sebagai token digital yang berbentuk seperti sertifikat kepemilikan untuk aset virtual dan fisik. NFT ini adalah biasanya diperdagangkan secara online dan sering dibayar untuk menggunakan cryptocurrency, khususnya Ethereum. Namun yang menjadi persoalan ialah pada tahun 2021 MUI pernah memfatwakan haram penggunaan cryptocurrency karena mengandung unsur gharar, dharar, dan qimar. Untuk itu, diperlukan kajian metodologi hukum Islam tentang Non-Fungible Token (NFT) melalui istihsan. Penelitian ini menggunakan pendekatan kualitatif. Sementara metode pengumpulan data yang dipakai dalam penelitian ini adalah metode literatur, dokumentasi dan observasi. Dalam menganalisis data yang telah dikumpulkan, peneliti menggunakan analisis deskriptif-analitis dengan pendekatan ushuliyah. Hasil penelitian ini menyatakan bahwa dalam tinjauan istihsan, transaksi dengan menggunakan Non-Fungible Token diperbolehkan. Hal ini dikarenakan dalam tinjauan qiyas khafi, NFT dikenal asset yang mendasari transaksi tersebut (underlying assets). Hingga dalam tataran operasionalnya, bila qiyas khafy lebih besar manfaatnya, maka qiyas jaly itu boleh ditinggalkan dan yang dipakai adalah qiyas khafy demi terpeliharanya prinsip-prinsip maqasid syari’ah. Oleh karena itu, dalam kerangka istihsan, transaksi Non-Fungible Token diperbolehkan melalui qiyas khafi dikarenakan adanya unsur maslahat yang lebih besar.Keywords: Non-Fungible Token; Istihsan; Maqashid Syari’ah.